Europejska polityka energetyczna a globalny scenariusz redukcji emisji CO2 - Wolska, Patrycja (European Energy Policy and Global Scenario for CO2 Emission Reducing, 2008)
The paper describes "the game rules" of reducing CO2 defined in European Energy Policy. It shows the impact of Kyoto Protocol commitments on determining this policy and discusses the actual terms and trends in global energy sector identified by McKinsey Company. The main targets of the European Energy Policy defined in the Presidency Conclusions of Council of the European Union in March 2007 and the main scenarios how to reach them are presented. These targets, called "3 x 20 by 2020", are: reduction of greenhouse gases by 20%, improving energy efficiency by 20%, and raising the share of renewable energy in the energy mix to 20 % - all these by the year 2020. The final section of this paper presents implications of the European Energy Policy for Polish energy sector and the problems to achieve their objectives.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 215-230